A facile approach for graphdiyne preparation under atmosphere for an advanced battery anode. Issue 57 (5th July 2017) - Zuo, Zicheng; Shang, Hong; Chen, Yanhuan; Li, Jiaofu; Liu, Huibiao; Li, Yongjun; Li, Yuliang
Abstract : An explosion approach was developed for efficiently preparing graphdiynes (GDYs) at 120 °C in air without any metal catalyst. Abstract : An explosion approach was developed for efficiently preparing graphdiynes (GDYs) at 120 °C in air without any metal catalyst. The GDYs show great superiority in terms of thermal stability, conductivity (20 S m −1 ) and surface area (up to 1150 m 2 g −1 ), and can be applied as promising anodes for storing lithium/sodium ions.